Libraries electronic catalogs in the struggle for users: «old» and new approaches - G. A. Skaruk (Библиосфера, 2016)
Online Public Access Catalog (OPAC) is considered as a tool to ensure the usefulness and attractiveness of libraries for users. Modern approaches to make a search in OPAC effective and convenient, to satisfy the requirements and expectations of readers are characterized. The views of researchers and practitioners in this regard are compared.